2009
DOI: 10.1039/b816511d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic behaviour of alkylcobaloximes and imino-oxime complexes related to vitamin B12

Abstract: The ligand substitution reactions of complexes of the type trans-[(R)Co(Chel)S](+/0) with L, where chel = (DO)(DOH)pn = 2,2'-(1,3-diaminopropanebis(2-methyl-3-butanone)oxime), R = CH(3), L = imidazole, pyrazole, 1,2,4-triazole and 1-methylimidazole, and S = water and MeOH, and chel = (Hdmg)(2) = bis(dimethylglyoximate), R = CH(2)Cl, CH(2)Br, and CH(2)I, L = thiourea and pyridine, and S = water, were studied in detail as a function of temperature and pressure. The reported activation parameters (DeltaH, DeltaS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Nonetheless, both species typically bear a L-type ligand (L = neutral ligand; commonly a weak Lewis base) in the trans position relative to the R group, and substantial work on the influence of these ligands on the nature of the cobalt–carbon bond, and vice versa , has been performed. 9,10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, both species typically bear a L-type ligand (L = neutral ligand; commonly a weak Lewis base) in the trans position relative to the R group, and substantial work on the influence of these ligands on the nature of the cobalt–carbon bond, and vice versa , has been performed. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…ligands on the nature of the cobalt-carbon bond, and vice versa, has been performed. 9,10 On the other hand, significantly less attention has been devoted to vitamin B 12 model systems bearing X-type ligands (X = monoanionic ligand) in the analogous trans position. 11,12 A related family of Co III complexes is based on TIM (2,3,9,10tetramethyl-1,4,8,11-tetraazacyclotetradeca-1,3,8,10-tetraene; type C in Scheme 1), where the Co III center is substantially more electron-deficient than those in types A and B due to TIM being neutral.…”
Section: Introductionmentioning
confidence: 99%
“…The specific action of the grouping towards nickel ions has been attributed to the anti isomers of the compounds. A major aim to study such compounds originated from the fact that these types of ligand showed biological importance [1][2][3][4][5][6][7]. Oximes and dioximes have often been used as chelating ligand in the field of coordination chemistry and their metal complexes have been of great interest for many years.…”
Section: Introductionmentioning
confidence: 99%
“…The specific action of the grouping towards nickel ions has been attributed to the anti isomers of the compounds. A major aim to study such compounds originates from the fact that these types of ligands shows biological importance [4,10]. Oximes and dioximes have often been used as chelating ligands in the field of coordination chemistry and their metal complexes have been of great interest for many years.…”
Section: Introductionmentioning
confidence: 99%